Hygiene dan sanitasi pada beberapa rumah makan. Studi kasus di Kecamatan Darul Kamal, Aceh Besar - Syahrizal Syahrizal (Politeknik Kesehatan Kemenkes Aceh, 2022)
Background: The cleanliness of food utensils in restaurants is the most important part of assessing the quality of food and beverages. Poor hygiene and sanitation of cutlery used in serving food impact organisms so that they can multiply and contaminate food. In addition, food can be contaminated with bacteria through unclean eating utensils.Objective: This study aims to describe hygiene and sanitation in several restaurant businesses in the Darul Kamal sub-District, Aceh Besar.Method: This descriptive study used a cross-sectional design in the Darul Kamal sub-District in 2021. The sample consisted of 30 restaurant managers. Data were collected through interviews, and observations were made using a checklist. The data collected include the restaurant's characteristics, hygiene, and sanitation (equipment and place). Processing is carried out in stages, from editing, coding, entry, and cleaning—analysis using frequency distribution and descriptive.Results: The results showed that the food processors at several restaurants in the Darul Kamal sub-District, Aceh Besar, were aged 30-40 years and generally had junior high school education. The condition of hygiene, sanitation of food, and eating utensils in most restaurants has met the requirements (86.7% & 80.0%). Meanwhile, the sanitation of food processing places that have met the requirements is only 73.3%.Conclusion: The hygiene and sanitation of restaurants in the Darul Kamal sub-district have met health requirements and standards, so it is feasible to develop a better business.